Warped- AdS 3 black holes with scalar halo - Giribet, Gaston Enrique (2015)
We construct a stretched (aka Warped) Anti-de Sitter black hole in 3 dimensions supported by a real scalar field configuration. The latter is regular everywhere outside and on the horizon. No hair theorems in 3 dimensions demand the matter to be coupled to the curvature in a non-minimal way; however, this coupling can still be of the Horndeski type, i.e. yielding second order field equations similar to those appearing in the context of Galileon theories. These Warped-Anti-de Sitter black holes exhibit interesting thermodynamical properties, such as finite Hawking temperature and entropy. We compute the black hole entropy in the gravity theory and speculate with the possibility of this to admit a microscopic description in terms of a dual (Warped) Conformal Field Theory. We also discuss the inner and outer black hole mechanics.